Protein-Truncating Variants at the Cholesteryl Ester Transfer Protein Gene and Risk for Coronary Heart Disease. Issue 1 (23rd June 2017) - Nomura, Akihiro; Won, Hong-Hee; Khera, Amit V.; Takeuchi, Fumihiko; Ito, Kaoru; McCarthy, Shane; Emdin, Connor A.; Klarin, Derek; Natarajan, Pradeep; Zekavat, Seyedeh M.; Gupta, Namrata; Peloso, Gina M.; et al.
Abstract : Rationale : Therapies that inhibit CETP (cholesteryl ester transfer protein) have failed to demonstrate a reduction in risk for coronary heart disease (CHD). Human DNA sequence variants that truncate the CETP gene may provide insight into the efficacy of CETP inhibition. Objective: : To test whether protein-truncating variants (PTVs) at the CETP gene were associated with plasma lipid levels and CHD. Methods and Results: : We sequenced the exons of the CETP gene in 58 469 participants from 12 case–control studies (18 817 CHD cases, 39 652 CHD-free controls). We defined PTV as those that lead to a premature stop, disrupt canonical splice sites, or lead to insertions/deletions that shift frame. We also genotyped 1 Japanese-specific PTV in 27561 participants from 3 case–control studies (14 286 CHD cases, 13 275 CHD-free controls). We tested association of CETP PTV carrier status with both plasma lipids and CHD. Among 58 469 participants with CETP gene-sequencing data available, average age was 51.5 years and 43% were women; 1 in 975 participants carried a PTV at the CETP gene. Compared with noncarriers, carriers of PTV at CETP had higher high-density lipoprotein cholesterol (effect size, 22.6 mg/dL; 95% confidence interval, 18–27; P <1.0×10 −4 ), lower low-density lipoprotein cholesterol (−12.2 mg/dL; 95% confidence interval, −23 to −0.98; P =0.033), and lower triglycerides (−6.3%; 95% confidence interval, −12 to −0.22; P =0.043). CETP PTV carrier status was associated with reduced risk for CHD (summary odds ratio, 0.70; 95% confidence interval, 0.54–0.90; P =5.1×10 −3 ). Conclusions: : Compared with noncarriers, carriers of PTV at CETP displayed higher high-density lipoprotein cholesterol, lower low-density lipoprotein cholesterol, lower triglycerides, and lower risk for CHD. Abstract : Supplemental Digital Content is available in the text.